Expansion and evolutionary patterns of GDSL-type esterases/lipases in Rosaceae genomes - Yunpeng Cao; Yahui Han; Dandan Meng; Muhammad Abdullah; Jiangliu Yu; Dahui Li; Qing Jin; Yi Lin; Yongping Cai (Functional & Integrative Genomics, 2018)

Dendrocoumarin: a new benzocoumarin derivative from the stem of Dendrobium nobile - Xue-Ming Zhou; Bin Zhang; Guang-Ying Chen; Chang-Ri Han; Kun-Chi Jiang; Ming-Yue Luo; Bo-Zheng Meng; Wen-Xin Li; Shi-Dai Lin (Natural Product Research, 2018)

Natural and synthetic flavonoids, novel blockers of the volume-regulated anion channels, inhibit endothelial cell proliferation - Yucong Xue; Honglin Li; Yuanyuan Zhang; Xue Han; Gaohua Zhang; Wenya Li; Huiran Zhang; Yue Lin; Pingping Chen; Xiaorun Sun; Yalei Liu; Li Chu; et al. (Pflügers Archiv - European Journal of Physiology, 2018)

Bioaccumulation and Cycling of Polycyclic Aromatic Hydrocarbons (PAHs) in Typical Mangrove Wetlands of Hainan Island, South China - Yao-Wen Qiu; Han-Lin Qiu; Jun Li; Gan Zhang (Archives of Environmental Contamination and Toxicology, 2018)

Docking study and antiosteoporosis effects of a dibenzylbutane lignan isolated from Litsea cubeba targeting Cathepsin K and MEK1 - Wei Peng; Hui Shen; Bing Lin; Ping Han; Changhui Li; Qiaoyan Zhang; Bingzhu Ye; Khalid Rahman; Hailiang Xin; Luping Qin; Ting Han (Medicinal Chemistry Research, 2018)

Dynamic response of a dip slope with multi-slip planes revealed by shaking table tests - Hung-Hui Li; Cheng-Han Lin; Wei Zu; Chi-Chieh Chen; Meng-Chia Weng (Landslides, 2018)

Systematic analysis and comparison of the PHD-Finger gene family in Chinese pear (Pyrus bretschneideri) and its role in fruit development - Yunpeng Cao; Yahui Han; Dandan Meng; Muhammad Abdullah; Dahui Li; Qing Jin; Yi Lin; Yongping Cai (Functional & Integrative Genomics, 2018)

Association between prenatal nickel exposure and preterm low birth weight: possible effect of selenium - Xiaojie Sun; Yangqian Jiang; Wei Xia; Shuna Jin; Wenyu Liu; Xin Lin; Hongxiu Liu; Xiaomei Chen; Yang Peng; Han Li; Bin Lu; Shunqing Xu; et al. (Environmental Science and Pollution Research, 2018)

Serum Copper Homeostasis in Hypertensive Intracerebral Hemorrhage and its Clinical Significance - Ming Han; Shan Ding; Yuan Zhang; Zhexuan Lin; Kangsheng Li (Biological Trace Element Research, 2018)

Characterization of complete mitochondrial genomes of Mastacembelus erythrotaenia and Mastacembelus armatus (Synbranchiformes: Mastacembelidae) and phylogenetic studies of Mastacembelidae - Chong Han; Qiang Li; Jianfeng Lin; Zhipeng Zhang; Jianrong Huang (Conservation Genetics Resources, 2018)

Taraxasterol suppresses the growth of human liver cancer by upregulating Hint1 expression - Tianhao Bao; Yang Ke; Yifan Wang; Weiwei Wang; Yuehua Li; Yan Wang; Xiang Kui; Qixin Zhou; Han Zhou; Cheng Zhang; Dongming Zhou; Lin Wang; et al. (Journal of Molecular Medicine, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

Study on immobilization of marine oil-degrading bacteria by carrier of algae materials - Yiran Zhang; Wei Gao; Faxiang Lin; Bin Han; Changfei He; Qian Li; Xiangxing Gao; Zhisong Cui; Chengjun Sun; Li Zheng (World Journal of Microbiology and Biotechnology, 2018)

Umbilical Cord Mesenchymal Stem Cells Conditioned Medium Promotes Aβ25-35 phagocytosis by Modulating Autophagy and Aβ-Degrading Enzymes in BV2 Cells - Zhihao Xu; Wenbin Nan; Xiaoyue Zhang; Yuliang Sun; Jichao Yang; Kecheng Lu; Yalin Liu; Yaoxin Gao; Fen Yang; Wenchao Mao; Xuekun Xing; Jiang Du; et al. (Journal of Molecular Neuroscience, 2018)

Phthalate esters distribution in coastal mariculture of Hong Kong, China - Zhang Cheng; Han-Han Li; Lin Yu; Zhan-Biao Yang; Xiao-Xun Xu; Hong-Sheng Wang; Ming-Hung Wong (Environmental Science and Pollution Research, 2018)

Effect of Cu(II) on the stability of oxyanion-substituted schwertmannite - Junfei Li; Yingying Xie; Guining Lu; Han Ye; Xiaoyun Yi; John R. Reinfelder; Zhang Lin; Zhi Dang (Environmental Science and Pollution Research, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

Species-based classification reveals spatial processes of phytoplankton meta-communities better than functional group approaches: a case study from three freshwater lake regions in China - Li-Juan Xiao; Yiqiu Zhu; Yang Yang; Qiuqi Lin; Bo-Ping Han; Judit Padisák (Hydrobiologia, 2018)

Phylogeography of the Asian lesser white-toothed shrew, Crocidura shantungensis, in East Asia: role of the Korean Peninsula as refugium for small mammals - Seo-Jin Lee; Mu-Yeong Lee; Liang-Kong Lin; Y. Kirk Lin; Yuchun Li; E-Hyun Shin; Sang-Hoon Han; Mi-Sook Min; Hang Lee; Kyung Seok Kim (Genetica, 2018)

Rigenolides D–H, norsecoiridoid and secoiridoids from Gentiana rigescens Franch - Yoshihiro Suyama; Naonobu Tanaka; Kazuyoshi Kawazoe; Kotaro Murakami; Shun-Lin Li; Han-Dong Sun; Yoshiki Kashiwada (Journal of Natural Medicines, 2018)

Knockout of CTNNB1 by CRISPR-Cas9 technology inhibits cell proliferation through the Wnt/β-catenin signaling pathway - Lihong Guan; Shaoyi Zhu; Yawei Han; Ciqing Yang; Yanli Liu; Liang Qiao; Xiaoying Li; Han Li; Juntang Lin (Biotechnology Letters, 2018)

The different influence of the residual layer on the development of the summer convective boundary layer in two deserts in northwest China - Zhao Lin; Han Bo; Lv Shihua; Wen Lijuan; Meng Xianhong; Li Zhaoguo (Theoretical and Applied Climatology, 2018)

Sumoylation of SUVR2 contributes to its role in transcriptional gene silencing - Yu-Xi Luo; Yong-Feng Han; Qiu-Yuan Zhao; Jin-Lu Du; Kun Dou; Lin Li; She Chen; Xin-Jian He (Science China Life Sciences, 2018)

Sonic Hedgehog Regulation of the Neural Precursor Cell Fate During Chicken Optic Tectum Development - Ciqing Yang; Xiaoying Li; Qiuling Li; Han Li; Liang Qiao; Zhikun Guo; Juntang Lin (Journal of Molecular Neuroscience, 2018)

Spa therapy (balneotherapy) relieves mental stress, sleep disorder, and general health problems in sub-healthy people - Bei Yang; Qi-zhong Qin; Ling-li Han; Jing Lin; Yu Chen (International Journal of Biometeorology, 2018)

The Distal Gut Bacterial Community of Some Primates and Carnivora - Xiu Chen; Qin-Yuan Li; Gui-Ding Li; Fang-Ji Xu; Li Han; Yi Jiang; Xue-Shi Huang; Cheng-Lin Jiang (Current Microbiology, 2018)